The Long Non-Coding Antisense RNA JHDM1D-AS1 Regulates Inflammatory Responses in Human Monocytes - Malmström, Erik; Khan, Hina N.; Veer, Cornelis van ‘t; Stunnenberg, Melissa; Meijer, Mariska T.; Matsumoto, Hisatake; Otto, Natasja A.; Geijtenbeek, Teunis B. H.; de Vos, Alex F.; Poll, Tom van der; Scicluna, Brendon P. (Frontiers in cellular and infection microbiology, 2022)
Monocytes are key players in innate immunity, with their ability to regulate inflammatory responses and combat invading pathogens. There is a growing body of evidence indicating that long non-coding RNA (lncRNA) participate in various cellular biological processes, including the innate immune response. The immunoregulatory properties of numerous lncRNAs discovered in monocytes remain largely unexplored. Here, by RNA sequencing, we identified a lncRNA JHDM1D-AS1, which was upregulated in blood monocytes obtained from patients with sepsis relative to healthy controls. JHDM1D-AS1 expression was induced in primary human monocytes exposed to Toll-like receptor ligands, such as lipopolysaccharide (LPS), or bacteria. The inducibility of JHDM1D-AS1 expression in monocytes depended, at least in part, on nuclear factor–κB activation. JHDM1D-AS1 knockdown experiments in human monocyte-derived macrophages revealed significantly enhanced expression of inflammatory mediators, before and after exposure to LPS, relative to control cells. Specifically, genes involved in inflammatory responses were upregulated (e.g., CXCL2 , CXCL8 , IL1RN , TREM1 , TNF , and IL6 ), whereas genes involved in anti-inflammatory pathways were downregulated (e.g., SOCS1 and IL10RA ). JHDM1D-AS1 overexpression in a pro-monocytic cell line revealed diminished pro-inflammatory responses subsequent to LPS challenge. Collectively, these findings identify JHDM1D-AS1 as a potential anti-inflammatory mediator induced in response to inflammatory stimuli.